Regulating unfair banking practices in Europe : the case of personal suretyships - Weatherill, Stephen, 1961-; Ciacchi, Aurelia Colombi (Oxford : Oxford University Press, 2010)
Private persons frequently guarantee business debt incurred by family members, friends, or employers, often while unaware of the financial risk they are exposing themselves to. This book provides an analysis of the law's response to potential unfairness in the practice across 22 EU Member States, setting an agenda for legal reform.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Suretyship and guaranty -- European Union countries; Consumer credit -- Law and legislation -- European Union countries